Emotional And Moral Development in Pesantren: A Case Study of Ma'had Baitul Qur'an Madura - Halim, Abdul; Fahruddin, Ahmad Hanif; Alfiyatin, Yuliana (Molang: Journal Islamic Education, 2024)
This study examines the influence of pesantren traditions, such as Ta’zim, on the emotional and moral development of santri at Ma'had Baitul Qur'an Madura. The purpose of this study is to understand how the social environment and pesantren traditions shape the moral and emotional character of santri. The research method used is qualitative with a case study approach, involving participatory observation and in-depth interviews with santri and teachers. The results show that pesantren traditions, such as Ta’zim and gotong royong, create an environment conducive to the development of positive morals and emotions, such as empathy and a sense of social responsibility. The findings support Kohlberg's theory of moral development and affirm the importance of social interaction in individual moral formation. The implication of this study is that the pesantren tradition can be an effective model of character education, providing new insights for the development of moral education curricula in various contexts.